2022
DOI: 10.3390/ma15031031
|View full text |Cite
|
Sign up to set email alerts
|

A New Anorganic Equine Bone Substitute for Oral Surgery: Structural Characterization and Regenerative Potential

Abstract: Different xenogeneic inorganic bone substitutes are currently used as bone grafting materials in oral and maxillo-facial surgery. The aim of the present study was to determine the physicochemical properties and the in vivo performance of an anorganic equine bone (AEB) substitute. AEB is manufactured by applying a process involving heating at >300 °C with the aim of removing all the antigens and the organic components. AEB was structurally characterized by scanning electron microscopy (SEM), X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Addis et al 4 showed that anorganic equine bone exhibits morpho‐structural characteristics similar to those of bovine anorganic bone. 4 In the study by Poli et al., 33 13 patients undergoing alveolar ridge reconstruction prior to implant placement were treated using a titanium mesh and a combination of autologous bone and deproteinized bovine anorganic bone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Addis et al 4 showed that anorganic equine bone exhibits morpho‐structural characteristics similar to those of bovine anorganic bone. 4 In the study by Poli et al., 33 13 patients undergoing alveolar ridge reconstruction prior to implant placement were treated using a titanium mesh and a combination of autologous bone and deproteinized bovine anorganic bone.…”
Section: Discussionmentioning
confidence: 99%
“…Addis et al 4 showed that anorganic equine bone exhibits morpho‐structural characteristics similar to those of bovine anorganic bone. 4 In the study by Poli et al., 33 13 patients undergoing alveolar ridge reconstruction prior to implant placement were treated using a titanium mesh and a combination of autologous bone and deproteinized bovine anorganic bone. In 92.30% of the patients, the postoperative course was uneventful, and all patients achieved a sufficient increase in the thickness of the alveolar crest, allowing for proper placement of the planned dental implants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anorganic equine bone has been recently introduced as an alternative for bone grafting, used in oral surgery for volume preservation and for augmentation purposes. The aim of the study performed by Addis et al [ 5 ] was to assess the physicochemical and structural properties of anorganic equine bone and its in vivo performance in mandibular bony defects. The study confirmed that its structural and physicochemical properties match the typical features of heat-treated xenogeneic bone substitutes, and its use as a grafting material yielded bone formation with no presence of inflammatory cell infiltrate [ 5 ].…”
mentioning
confidence: 99%